Rapid and Specific Method for Evaluating Streptomyces Competitive Dynamics in Complex Soil Communities - Schlatter, Daniel C. (American Society for Microbiology (ASM), 2010)
Quantifying target microbial populations in complex communities remains a barrier to studying species interactions in soil environments. Quantitative PCR (qPCR) assays were developed for quantifying pathogenic Streptomyces scabiei and antibiotic-producing Streptomyces lavendulae strains in complex soil communities. This assay will be useful for evaluating the competitive dynamics of streptomycetes in soil.